DPK, CAR, NPF, DER, DAN ROA TERHADAP PEMBIAYAAN MURABAHAH PADA BANK UMUM SYARIAH - Mr Mizan (UMSurabaya Publishing, 2017)
ABSTRACT This research aim to know the influence of DPK, CAR, NPF, DER and ROA with murabahah financing the Islamic Banks in Indonesia. The type of this research was an associative research. This research is aimed at finding out the significant influence of Profit Margin and Non Performing Financing (NPF) toward Murabahah FinancingThe Islamic Banks in Indonesia. There were two independent variabels of this research, namely: profit margin and Non Performing Financing (NPF). The data sources were secondary data. To collect the data, the researcher used documentation. This research was a quantitative analysis. To analyze the data, the researcher used multiple regression. The results showed that distribution the profit margin and Non Performing Financing (NPF) had significant influence toward distribution of murabahah financing, otherwiseCapital Adequacy Ratio (CAR), Return On Assets (ROA), Debt to Equity Ratio (DER) variables uninflunce on financing murabhahahThe Islamic Banks in IndonesiaKey words : Murabahah Financing, Third Party Fund, CAR, NPF, DER, ROACorrespondence to : m124n24@gmail.com ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh Dana Pihak Ketiga, Capital adequacy rasio, non performing financing, Dept to equity rasio, Retrun on assets terhadap penyaluran pembiayaan murabahah pada Umum Syariah di Indonesia.Penelitian ini termasuk penelitian asosiatif untuk mengetahui hubungan pengaruh antara variabel independen Dana Pihak Ketiga, Capital adequacy rasio, non performing financing, Dept to equity rasio, Retrun on assets terhadap variabel dependen pembiayaan murabahah. Data yang digunakan dalam penelitian ini adalah data sekunder. Teknik pengumpulan datanya adalah dokumentasi. Analisis data yang digunakan adalah analisis kuantitatif yang menggunakan regresi berganda. Hasil analisis secara keseluruhan pada saat periode penelitian menunjukkan bahwa dana pihak ketiga dan Non Performing Financing (NPF) berpengaruh signifikan terhadap penyaluran pembiayaan murabahah, sebaliknya variabel Capital Adequacy rasio (CAR), Return On Assets (ROA), Debt to Equity Rasio (DER )tidak berpengaruh terhadap pembiayaan murabhahah pada Bank Umum Syariah di Indonesia.Kata kunci : Pembiayaan Murabahah, Dana Pihak Ketiga, CAR, NPF, DER, ROAKorespondensi : m124n24@gmail.com